Agro-Morphological Characterization and Intra-Varietal Diversity of Akabarechilli (Capsicum spp.) Landraces of Nepal (SAARC Journal of Agriculture, 2022)
Capsicum (Solanaceae), comprising of sweet and hot chilli pepper, is a globally known spice crop. This genus is well known for its huge genetic diversity at intra- and inter-species level. Diversity among Akabarechilli landraces, a unique Capsicum from Nepal, has not been studied so far. The present study characterized thirty accessions of Akabarechilli using 26 qualitative and 21 quantitative agro-morphological markers at the experimental plots of National Genebank, Khumaltar, Nepal during the summer season of 2018/019. Using principal component analysis, the first- principal components with eigen-values more than 1 contributed 25% of the variability among accessions for quantitative traits, whereas the first principal components with eigen-values more than 1 contributed 22.2% of the variability among accessions for qualitative traits. These findings suggested a wide range of morphological variations among the tested accessions. Based on qualitative and quantitative traits, 30 accessions were grouped into 6 distinct clusters by Euclidian distance and average method. Accessions CO-11048 and CO-11050 under cluster-III were round shape fruit type and accessions CO-11044, CO- 11046 andCO-11047 under cluster-I were high fruiting with longer fruitbearing period and could be utilized for breeding purpose as these are the traits preferred by consumers or processors in Nepalese market.SAARC J. Agric., 19(2): 37-55 (2021)